Protective effect of Saussurea involucrata polysaccharide against skin dryness induced by ultraviolet radiation - Wang, Lusheng; Yang, Kaiye; Jing, Rongrong; Zhao, Wengang; Guo, Keke; Hu, Zhenlin; Liu, Guangrong; Xu, Nuo; Zhao, Jungang; Lin, Li; Gao, Shuang (Frontiers in Pharmacology, 2023)
Background: Exposure to ultraviolet B (UVB) radiation can damage the epidermis barrier function and eventually result in skin dryness. At present, little work is being devoted to skin dryness. Searching for active ingredients that can protect the skin against UVB-induced dryness will have scientific significance. Methods:Saussurea involucrata polysaccharide (SIP) has been shown to have significant antioxidant and anti-photodamage effects on the skin following UVB irradiation. To evaluate the effect of SIP on UVB-induced skin dryness ex vivo, SIP-containing hydrogel was applied in a mouse model following exposure to UVB and the levels of histopathological changes, DNA damage, inflammation, keratinocyte differentiation, lipid content were then evaluated. The underlying mechanisms of SIP to protect the cells against UVB induced-dryness were determined in HaCaT cells. Results: SIP was found to lower UVB-induced oxidative stress and DNA damage while increasing keratinocyte differentiation and lipid production. Western blot analysis of UVB-irradiated skin tissue revealed a significant increase in peroxisome proliferator-activated receptor-α (PPAR-α) levels, indicating that the underlying mechanism may be related to PPAR-α signaling pathway activation. Conclusions: By activating the PPAR-α pathway, SIP could alleviate UVB-induced oxidative stress and inhibit the inflammatory response, regulate proliferation and differentiation of keratinocytes, and mitigate lipid synthesis disorder. These findings could provide candidate active ingredients with relatively clear mechanistic actions for the development of skin sunscreen moisturizers.